Understanding sustainability transitions for urban informality in the Middle East - Ahmed M. Soliman (International Journal of Urban Sustainable Development, 2020)
In 2018, UN-Habitat projected the total population of the planet was about 7.632 billion. Fifty-five percent were living in urban areas in which more than 20 percent were said to live in slum areas. Within the era of increasing urbanization, and in the context of Habitat III, this article highlights planning innovation of the sustainability transition in urban informality in the Middle East. Three themes are raised. The first is to trace the recent academic debate on urban informality transitions in the Middle East. The second is to ask whether it possible to borrow new planning innovations from the Global North and apply them in the Global South and Middle East. Finally, the present work considers whether it is possible to link between the theory and the practice of governance of sustainability transitions and urban informality. It concludes that the configuration of urban informality in light of sustainability transitions would enhance the continuous sociotechnical and political transitions in the Middle East.